Prevalence of Hepatitis C among Lichen Planus Patients - Rabindra Sharma; Sushil Paudel (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: The association between hepatitis C virus (HCV) infection and lichen planus (LP) has been studied widely. Extrahepatic manifestations including lichen planus are common among patients infected with HCV. The prevalence of HCV among lichen planus (LP) seems to vary geographically.